The Tauhid Sufism Study Council (MPTT-I) and the Dynamics of Religious Spiritual Practice in Aceh, Indonesia : Majelis Pengkajian Tauhid Tasawuf (MPTT-I) dan Dinamika Praktik Sosial Keagamaan di Aceh, Indonesia - Saprijal; Rasyad; Manan, Abdul (Indonesian Journal of Islamic History and Culture, 2024)
This article discusses the movement of the Indonesian Tauhid Sufism Study Council (MPTT-I) which is one of the religious institutions engaged in the worship. This study uses a qualitative descriptive approach with primary data collected through observation, in-depth interviews, and documentation. Data was analyzed in accordance with qualitative descriptive methodology, following the process of data reduction, data presentation, and drawing conclusions. The results show that the MPTT-I movement formed zikr assemblies through a house-to-house approach, mosques, mushalla, and gave birth to cadres of young people who love Sufism, as well as Sufism women's associations at the provincial, district, sub-district, and village levels, imparting knowledge related to the Tauhid Sufism, serving the community in carrying out learning activities on Tauhid Sufism, and inviting all levels of society to increase awareness of Islamic principles. Spiritual practice, namely reciting the zikr la ila ha ilAllah at least 300-500 times after each prayer, shalawat at least 30 times to the Prophet Muhammad, always trying to pray in congregation at the mosque, attending religious studies, maintaining social values, obeying the orders of leaders (if still in the path of goodness), avoiding hostility, and creating unity regardless of tribe and position.